Centennial-scale gaps in a 5500-year acroporid growth trajectory from a Caribbean coral reef - Alexis Medina-Valmaseda; Paul Blanchon; Juan Pablo Bernal; Edlin Guerra-Castro; Liliana Corona-Martinez; Alexander Correa-Metrio (Royal Society Open Science, 2025)
Persistence of acroporid-dominated assemblages on Caribbean reefs throughout the Holocene and late Pleistocene implies that their rapid regional demise over the last 50 years is unprecedented. However, the palaeoecological trajectory of acroporid growth is largely unknown. Here, we reconstruct a 5500-year acroporid trajectory from a hurricane-prone fringing reef off the northeast Yucatan coast and find that growth is not constant but punctuated by centennial-scale gaps. Local coastal archives show these gaps coincide with hurricane-frequency anomalies, which is consistent with local extirpation of acroporids following intense hurricane strikes. On each devastated reef, acroporids took hundreds of years to recolonize their former habitat, probably owing to naturally impaired sexual recruitment combined with substrate deterioration. By comparing trajectories across the Caribbean, we show that extirpation-recolonization events occur at different times between reefs, so gaps do not coincide. The resulting regional constancy of this palaeoecological baseline affirms that the historical demise of acroporids is unprecedented over the last 14 000 years and portends their absence on degraded reefs for hundreds of years into the future unless mitigated by restoration.